2016
DOI: 10.1111/bjh.14344
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative management of anticoagulation and antiplatelet therapy

Abstract: The Grading of Recommendations Assessment, Development and Evaluation (GRADE) nomenclature was used to evaluate levels of evidence and to assess the strength of recommendations. The GRADE criteria are specified in the British Committee for Standards in Haematology (BCSH) guidance pack

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
178
1
30

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(210 citation statements)
references
References 78 publications
1
178
1
30
Order By: Relevance
“…In the context of GI bleeding, warfarin can be interrupted at presentation. It can be simply discontinued for a low-risk haemorrhage and, in addition, reversed in severe haemorrhage, with vitamin K and prothrombin complex concentrate if required 105. Overall, there is a mortality benefit from restarting warfarin once the LGIB has stopped 106–108.…”
Section: Drug Therapy Considerations In Acute Lgibmentioning
confidence: 99%
“…In the context of GI bleeding, warfarin can be interrupted at presentation. It can be simply discontinued for a low-risk haemorrhage and, in addition, reversed in severe haemorrhage, with vitamin K and prothrombin complex concentrate if required 105. Overall, there is a mortality benefit from restarting warfarin once the LGIB has stopped 106–108.…”
Section: Drug Therapy Considerations In Acute Lgibmentioning
confidence: 99%
“…There are two previously reported cases of haemorrhagic complications of neuraxial puncture in patients on clopidogrel, although in both cases the patients were on multiple antiplatelet agents 41 42. The BSH guidelines state that there is insufficient evidence that they are safe in neuraxial anaesthesia and so advise that clopidogrel, ticagrelor and prasugrel are stopped 7 days before procedures 8. This is in agreement with both American and European anaesthetic guidelines that advise stopping clopidogrel for 7 days before neuraxial anaesthesia due to its irreversible effects on platelet activation, which last for the lifespan of the platelet 3 4 19…”
Section: Antiplateletsmentioning
confidence: 67%
“…A systematic review and a meta-analysis both found no proof for the efficacy of bridging to prevent thromboses, but with increased rates of bleeding 8. In patients with atrial fibrillation, the BRIDGE (Perioperative Bridging Anticoagulation in Patients with Atrial Fibrillation) trial showed that no bridging was non-inferior to bridging in terms of arterial thromboembolism (p=0.01), with arterial thromboembolism occurring in 0.4% of the no bridging group, and 0.3% of the bridging group 28.…”
Section: Anticoagulantsmentioning
confidence: 99%
“…81 For patients with impaired renal function, it is advised that this interval be prolonged by 24 hours (or longer for dabigatran). 81 Patients undergoing procedures that carry a high bleeding risk should not recommence full dose postoperative anticoagulation until 48-72 hours following the procedure. 81 …”
Section: Perioperative Managementmentioning
confidence: 99%
“…81 Patients undergoing procedures that carry a high bleeding risk should not recommence full dose postoperative anticoagulation until 48-72 hours following the procedure. 81 …”
Section: Perioperative Managementmentioning
confidence: 99%